Problematyka prawna działek letniskowych: [Legal statuts of summer house lots] (Studia Prawnicze / The Legal Studies, 2023)
During the last years, because of big urban and industrial aglomerations and other consequences of modern life, there appeared the tendency to own a land lot with a summer house and it is now more and more perceivable, This is so because it seems that a summer house gives maximum freedom to its owner. However, building of summer houses interferes with various fields of socio-economic life and since it is now a phenomenon of mass character, it is necessary to look for solutions which would allow to keep this type of building in reasonable frames and at the same time protect against taking over the land not designated for recreation purposes (e.g. farms, forests subject to specific protection because of landscape or natural values, etc.).This article presents legal problems of summer house lots; procedure of appointing parts of land for recreation purposes, alotting the lots for the purpose of individual recreation, problems of the norms of area. Also, heretofore used methods and legal grounds of acquisition of summer house lots are presented, as well as negative consequences of informal transfer of lots which constitute parts of land designated for the purpose of farming. The Author also discusses highly unsatisfactory state of binding legal rules in this domain, aimed at protecting the land against the use which is irrational or contrary to the designation.Final part of this article contains propositions concerning specific legislative changes which would subject summer house lots to the principles common for administration of land within the town limits, also as far as statutory right of pre-emption is concerned. This would eliminate elements such as spontaneity, chance, discretion and speculation from the process of acquisition and use of plots designated for construction of summer houses.